P875 Disease course of Ulcerative Colitis during the first ten years following diagnosis in a prospective European population-based inception cohort – the Epi-IBD cohort. (30th January 2023) - Wewer, M D; Salupere, R; Kievit, H A L; Nielsen, K R; Midjord, J; Domislovic, V; Krznarić, Ž; Pedersen, N; Jens, K; Eriksson, C; Halfvarson, J; Talbot, A; et al.
Abstract: Background: The Epi-IBD cohort is a prospective European population-based cohort of 1, 390 patients diagnosed in 2010 and 2011 with inflammatory bowel disease (IBD) according to Copenhagen criteria in centres from Eastern and Western European countries. The study aims at describing differences in incidence, treatment strategies, disease course and prognosis of ulcerative colitis (UC) Eastern and Western Europe. Methods: UC patients were followed prospectively from the time of diagnosis until December 31 st, 2020, death, emigration or loss of follow-up. Clinical data on surgery, hospitalizations and medical treatment were captured throughout the follow-up period and entered in a validated web-database, www.epi-ibd.org . Associations between colectomy and covariates were analysed by multivariate Cox regression analyses. Results: A total of 816 UC patients aged ≥15 years from 21 centres in 5 Eastern and 11 Western European countries were included. Overall, 51 (6%) patients underwent colectomy. A total of 190 (23%) patients were hospitalized at least once for their UC. Cancer was diagnosed in 28 (3%) patients, including 4 colorectal cancers. The use of medical therapy was comparable across Eastern and Western European centres (Table 1). During follow-up, 121 out of 776 (16%) patients with limited UC (proctitis or left-sided colitis) progressed to extensive colitis. The median time to progression was 21 (IQR: 8-48) months from diagnosis. No patients from Eastern Europe were exposed to biological therapy prior to change in disease extent, compared to 6 out of 98 patients (6%) from Western Europe. Multivariate Cox regression analysis showed no difference in risk of colectomy according to European region (Eastern vs. Western Europe, HR: 1.05, 95%CI: 0.48-2.29). Early intervention with biologicals (within 6 months) was associated with higher risk of colectomy (HR: 3.06, 95% CI: 1.23-7.58), and so was early introduction of immunomodulators (HR: 2.35, 95%CI: 1.16-4.76). Progression in disease extent to extensive colitis was significantly associated with higher risk of surgery (HR: 5.30, 95% CI: 2.36-11.90) and similarly extensive colitis at diagnosis compared to proctitis (HR: 3.48, 95% CI: 1.12-10.82). Conclusion: After 10 years of follow up in this European multicentre study, only 6% percent had a colectomy performed. Despite the widespread use of immunomodulators and biologicals, 16% of patients with limited disease extent progressed to extensive colitis which was associated with higher risk of surgery. The need for early introduction of biological therapy and immunomodulators might predict risk of surgery.